EFFECTS OF THERMOCYCLING AND VARIOUS DRINKS ON THE COLOR STABILITY OF HEAT-POLYMERIZED ACRYLIC RESIN - Altinci P; Durkaya P (ISTANBUL UNIV, FAC DENTISTRY, 2022)
Purpose: The discoloration of acrylic resin denture bases may lead to significant esthetic problems. The aim of this in vitro study was to investigate the effects of frequently consumed drinks on the color changes of fresh and aged, heat-polymerized, conventional acrylic resin.Materials and Methods: Eighty-four, heat-polymerized acrylic resin specimens (4 mm x 5 mm x 30 mm) were fabricated. Half of the specimens were aged by thermal cycling (between 5 degrees C and 55 degrees C, 60-second dwell time, 3000 cycles). The specimens were stored at 37 degrees C in different drinks as non-aged and aged subgroups including water (control group), black tea, green tea, sour cherry juice, coke and coffee (n=7). The discoloration of each specimen after 1 and 7 days storage in the drinks were measured by a colorimeter based on CIE Lab system. The data of colour differences (Delta E) were analyzed by ANOVA and Dunnet's tests.Results: Thermal cycling and storage in water induced a slight color change. The highest DE values were observed in the aged groups, which was also noticeable for black tea and sour cherry juice after 7 days of storage (Delta E>1.5) (p<0.05). The Delta E values of all test groups were detected within the acceptable clinical limits (Delta E<3.5).Conclusion: These results suggest that the color stability of denture base acrylic resins is influenced by ageing. Black tea, sour cherry juice and coke can cause significant discolorations on acrylic resin denture bases.